2021
DOI: 10.1038/s41398-020-01145-1
|View full text |Cite
|
Sign up to set email alerts
|

Long runs of homozygosity are associated with Alzheimer’s disease

Abstract: Long runs of homozygosity (ROH) are contiguous stretches of homozygous genotypes, which are a footprint of inbreeding and recessive inheritance. The presence of recessive loci is suggested for Alzheimer’s disease (AD); however, their search has been poorly assessed to date. To investigate homozygosity in AD, here we performed a fine-scale ROH analysis using 10 independent cohorts of European ancestry (11,919 AD cases and 9181 controls.) We detected an increase of homozygosity in AD cases compared to controls [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Our objective is also to select clusters with a sufficiently large number of individuals to correlate them with phenotypes. It is worth noting that in previous studies, a minimum cut-off of 100 individuals was commonly used ( Lencz et al, 2007 ; Christofidou et al, 2015 ; Moreno-Grau et al, 2021 ). On average ~18% of sites are heterozygous, and thus for a pair of 100 sites genotype sequences, there is a very small probability that they will be mapped to the same compressed haplotype.…”
Section: Resultsmentioning
confidence: 99%
“…Our objective is also to select clusters with a sufficiently large number of individuals to correlate them with phenotypes. It is worth noting that in previous studies, a minimum cut-off of 100 individuals was commonly used ( Lencz et al, 2007 ; Christofidou et al, 2015 ; Moreno-Grau et al, 2021 ). On average ~18% of sites are heterozygous, and thus for a pair of 100 sites genotype sequences, there is a very small probability that they will be mapped to the same compressed haplotype.…”
Section: Resultsmentioning
confidence: 99%
“…In humans, ROH are associated with numerous complex disease and non-disease phenotypes (Clark et al 2019; Johnson, Evans, and Keller 2018; Moreno-Grau et al 2021; Keller et al 2012; Bacolod et al 2008), and in dogs ROH have been associated with disease phenotypes (Mooney, Yohannes, and Lohmueller 2021; Sams and Boyko 2019; Boyko 2011). Previous studies have shown the influence of genetic variants in different quantitative traits such as leg length, wrinkled skin, coat color, hair length, and skeletal shape (Sutter et al 2007; Boyko et al 2010; Parker et al 2009; Cadieu et al 2009; Candille et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It is also likely that variants specific to individual populations, and thus difficult to detect with genome-wide ass1ociation study (GWAS) approaches unless the population is homogenous, may explain at least a portion of the missing heritability of EOAD. In addition, other inheritance patterns should be considered, e.g., autosomal recessive loci might cause EOAD ( Moreno-Grau et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%